Telling off Justinian: Theudebert I, the Epistolae Austrasicae, and communication strategies in sixth‐century Merovingian–Byzantine relations. - Gillett, Andrew (Early Medieval Europe, 2019)
The death of the powerful Frankish king Theudebert I (r. 533–47) gave rise to a diplomatic imbroglio between the courts of the eastern emperor Justinian, who condemned the late king, and Theudebert's son and successor Theudebald, who aggressively defended his father's memory. This dispute provides two opportunities: first, to parse the sixth‐century sources into separate political discourses; and secondly, to examine the diplomatic letters of Theudebert and Theudebald, preserved in the Gallic letter collection Epistolae Austrasicae, as evidence for creative experimentation with the genre of letters, expanding the functions and forcefulness of the basic media of long‐range communication.